Comparison of early period results of blood use in open heart surgery - Huseyin, Serhat (J Res Med Sci, 2016)
BACKGROUND: Various adverse effects of homologous blood transfusion detected particularly in open heart surgery, in which it is frequently used, lead researchers to study on autologous blood use and to evaluate the patient's blood better. Due to the complications of homologous blood transfusion, development of techniques that utilize less transfusion has become inevitable. We aimed to evaluate the effects of acute normovolemic hemodilution (ANH) in patients undergoing open heart surgery. MATERIALS AND METHODS: In this study, 120 patients who underwent open heart surgery were included. Patients were grouped into three: Autologous transfusion group (Group 1), homologous transfusion group (Group 2), and those received autologous blood and homologous blood products (Group 3). Patient data regarding preoperative characteristics, biochemical parameters, drainage, extubation time, duration of stay at intensive care, atrial fibrillation (AF) development, and hospital stay were recorded. RESULTS: A statistically significant difference (P < 0.005) was found in favor of autologous group (Group 1) with respect to gender, body surface area, European System for Cardiac Operative Risk Evaluation, smoking, hematocrit levels, platelet counts, urea, C-reactive protein levels, protamine use, postoperative drainage, frequency of AF development, intubation period, stay at intensive care and hospital stay, and amount of used blood products. CONCLUSION: The use of autologous blood rather than homologous transfusion is not only attenuates side effects and complications of transfusion but also positively affects postoperative recovery process. Therefore, ANH can be considered as an easy, effective, and cheap technique during open heart surgery.